2003
DOI: 10.1159/000071015
|View full text |Cite
|
Sign up to set email alerts
|

Are Amniotic Fluid Alpha-Fetoprotein Levels Influenced by the Gender in Twin Pairs?

Abstract: Objectives: To examine the assumption that amniotic fluid alpha-fetoprotein (AFAFP) levels are different in female and male twin fetuses. Design: Amniotic fluid levels of AFP in pregnancies with female and male fetuses in gender-concordant and gender-discordant twins were compared. A t test of p < 0.05 was considered significant. Material and Methods: Between 1995 and 1999, 332 genetic amniocenteses on twin pregnancies were performed at Meir Hospital, Kfar Saba, and Rambam Hospital, Haifa, Israel. One hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(8 reference statements)
1
0
0
Order By: Relevance
“…They concluded that in singleton or twin pregnancies, the AFP concentration in amniotic fluid is not affected by fetal gender [25] . A similar conclusion was reached by Sharony et al [26] . They observed that in gender discordant twins, the difference in the AFAFP concentrations is not statistically significant.…”
Section: Discussionsupporting
confidence: 87%
“…They concluded that in singleton or twin pregnancies, the AFP concentration in amniotic fluid is not affected by fetal gender [25] . A similar conclusion was reached by Sharony et al [26] . They observed that in gender discordant twins, the difference in the AFAFP concentrations is not statistically significant.…”
Section: Discussionsupporting
confidence: 87%